Sit write furniture - Ong, Jowin (2016)
The Sit Write furniture is an ergonomic furniture to be introduced into classrooms. The project identified that there is a one-size-fits-all problem that is unable to properly fit every student, which might lead to long-term health issues that are hard to correct over time. The project will look into the existing tables and chairs being used and aspires to rethink and redesign it into something which promotes a proper sitting posture. It will focus on Primary school students due to the ideal age range for the shaping of their spines. All in all, the Sit Write furniture hopes to make a difference to the wellness of our future generation.